Organizational Transformation Toward Agility: Integrating Change Management, Dynamic Capabilities, and MSME Adaptability - Munandar, Aris; Dwijanto Witjaksono2, Andre (JURISMA : Jurnal Riset Bisnis & Manajemen, 2025)
This study explores how organizational transformation can enhance the agility of Micro, Small, and Medium Enterprises (MSMEs) in West Nusa Tenggara (NTB), Indonesia, by integrating Change Management and Dynamic Capabilities approaches. Facing ongoing disruptions and global uncertainty, MSMEs in NTB struggle with limited financing, outdated technologies, and low digital adoption. Organizational agility is essential for responding quickly to market and technological shifts. Using an explanatory quantitative method, data were gathered from 310 MSME actors via a Likert-scale questionnaire and analyzed with SEM-PLS. The results show that change management significantly impacts agility (β = 0.412) and dynamic capabilities (β = 0.537). Dynamic capabilities also strongly influence agility (β = 0.384) and mediate the relationship between change management and agility. These findings highlight that effective change management strengthens the ability to adapt to external challenges. Practically, the study underscores the importance of internal transformation driven by strategic vision, dynamic resource management, and inclusive decision-making. Theoretically, it offers a new model for MSME resilience in regions facing digital divides. The integration of Change Management and Dynamic Capabilities proves vital for cultivating an agile, adaptive, and competitive MSME landscape in the era of digital transformation. Keywords : Change Management 1; Dynamic Capabilities 2; Organizational Agility 3; MSME Transformation 4; Business Adaptability 5